Peran Organisasional Terhadap Pengembangan Bahan Ajar Pengauditan Berbasis ISA : Perspektif Dosen Pengauditan - Asmara, Eka Noor; Supardi, Supardi; Ashari, Sidiq (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2016)
The adoption of International Standards on Auditing (ISA) by IAPI as a new auditing standard in Indonesia is unavoidable choice. As a consequences, alteration of teaching materials on higher education into ISA is considered as a necessary step that has to be taken. If the presumption of institutional isomorfism is taken place by IAPI, the feared of unwellprepared higher education and lectures in the process of adoption and integration new auditing standard has a reasonable reasons. This research is conducted to examine relationship of organization support and individual factor in the process of developing and teaching of audit course material to conform to ISA. Data collection in this research is based on survey that has been used in many similar researches. Training variable represent organization support as well as self-efficacy represent individual variable. Structural equation modeling is applied in this research. Finding of this research demonstrate that hypothesis of relationship between training and self-efficacy and teaching material is significantly supported so that this research elaborate institutional theory of institutional isomorphism. Finding of hypothesis examination indicates that organization support in the form of training could be a proper medium to increase lecturer competency especially in the ISA implementation. Furthermore, professionalism itself could be an important root for the creation of isomorphism norm.